Fe2O3/ZIF-8 architectures with enhanced thermocatalytic performance for efficient degradation of nitrocellulose. (March 2023) - Zhao, Ningning; Yu, Zhong; Ma, Haixia; Yao, Ergang; An, Ting; Zhao, Fengqi; Yu, Xiaojiao
Abstract: Fe2 O3 /zeolitic imidazolate framework-8 (ZIF-8) architectures were successfully prepared by a polyvinylpyrrolidone (PVP)-assisted method, which can be as an effective potential catalyst for promoting the thermal degradation of nitrocellulose (NC). Thermal behavior and degradation kinetics of catalyst-NC mixtures were studied using the TG/DTG and DSC methods, and found that the Fe2 O3 /ZIF-8-NC pyrolysis possessed a total degradation of 77.96%, a maximum pyrolysis rate temperature of 194.5 °C, and the lowest activation energy of 179.4 ± 16.1 kJ mol −1, confirming a better thermocatalytic performance of Fe2 O3 /ZIF-8 when compared to Fe2 O3 and ZIF-8 for NC thermolysis. Furthermore, it can be inferred from the isoconversional analysis, which employs a modified fitting algorithm, that catalyst-NC mixtures and pure NC adhere to the reconstructed "n-order" reaction models. This work showed how a catalyst of the metal oxide/metal-organic frameworks (MOFs) type could improve the pyrolysis of NC, which could serve as a significant reference for the development of additional catalysts of the metal oxide/MOFs for use in NC-based energetic materials. Graphical abstract: Image 1 Highlights: Catalytic effects of Fe2 O3 /ZIF-8 on NC pyrolysis process are investigated for the first time. Thermal and kinetic analysis of Fe2 O3 -NC, ZIF-8-NC and Fe2 O3 /ZIF-8-NC are performed comparatively. Fe2 O3 /ZIF-8 architectures exhibit superior catalytic property when compared to Fe2 O3 and ZIF-8.